Trends in Point of Care Ultrasound Familiarity Among Undergraduate Medical Clerkship Educators - Nilan Schnure; Mahmoud Mohamed Elfadil; Wilma Chan; Cameron Baston; Frances Shofer; Nova Panebianco (CINQUILL Medical Publishers Inc., 2024)
Objectives: Despite growing use of point of care ultrasound (POCUS), there remains a paucity of data about familiarity with POCUS among educators who dictate curricular content in undergraduate medical education. This paper aims to longitudinally characterize the level of comfort and frequency of POCUS use among faculty involved in undergraduate clerkship education. Methods: A web-based cross-sectional survey assessing comfort, frequency of use, and awareness of indications for POCUS among faculty involved in Internal Medicine, Family Medicine, and Surgery undergraduate clerkship education in a single urban academic medical center in 2016 and again in 2022. Results: A total of 45 responses from 2016 and 30 responses from 2022 are included. The percentage of faculty "not comfortable" with performing POCUS decreased from 78% to 46%, although the overall change in comfort was not statistically significant. Comfort interpreting POCUS images, frequency of POCUS use, and familiarity with the clinical applications of POCUS all improved. Faculty identified multiple barriers to more frequent POCUS use. Conclusions: Over a six-year period at one urban, academic medical center, comfort with POCUS and frequency of use have increased slightly but remain low among core faculty responsible for clerkship education. There are still large gaps in knowledge and very regularly use POCUS, which can be attributed to multiple different barriers.